The Effect of Dietary Chromium-Yeast on the Growth Performance of Baung Fish (Hemibagrus nemurus Blkr) - Endang Purnama Sari; Ing Mokoginta; Dedi Jusadi (Jurnal Ilmu-Ilmu Perairan dan Perikanan Indonesia, 2009)
A triplicate experiment was conducted to determine the effect of dietary chromium on the growth performance of baung fish (Hemibagrus nemurus Blkr). This experiment used four diets contain different level of chromium yeast (0.0, 1.47, 3.20, and 4.59 mg/kg). Twenty fish with the initial body weight 7.0 ± 0.2 g were placed in each aquarium (50x40x35 cm). Fish were fed on the experimental diets three times daily, at satiation for 60 days. The results showed that chromium diets produced body protein level, ratio RNA/DNA and protein retention higher than that of non chromim diet. However, diet contained chromium yeast 3.20 mg/kg produced the highest protein deposition. Finally, it also produced the highest daily growth rate and feed efficiency. The liver and carcass glycogen level increased as the chromium level of diets was elevated, on the other side, body lipid level decreased as the chromium level of diets was elevated.Keywords: chromium, baung, growth.